Relationship Between Electricity Consumption, Manufacturing Output and Financial Development: A New Evidence from Nigeria - Ibrahim, Saifullahi Sani; Mukhtar, Shuaibu; Gani, Ibrahim Musa (Energy Economics Letters, 2017)
Electricity is regarded as sine quo non for any meaningful social, economic and modern scientific advancement of any country in the world. It is regarded as a force and engine room of the industrial sector. However, in Nigeria, instability in power supply is negatively affecting manufacturing efficiency. Time series data for 1981 until 2015 was used to examine the symmetric relationship between the electric consumption, manufacturing output and financial development in Nigeria. The result indicates the co-movement in the variable over long time horizon, meaning that any inefficiency in electricity supply would impedes industrial output. Moreover, the Granger causality test based on vector error correction framework shows the presence of causality between power utilization of manufacturing firms and economic growth without feedback. In this sense it can be stress that stable electricity consumption is important factor for Nigeria’s manufacturing sector. The result of variance decomposition further indicates that the variation in the industrial output responds more to shocks in the electricity supply than its own shock. This finding suggests that energy is the engine of manufacturing sector in Nigeria.